(untitled) (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2025)
This study aims to investigate the implementation of the Scanning strategy to improve students’ reading comprehension. The research employed a pre-experimental design with a one-group pre-test and post-test model. The sample consisted of 30 students grades VIII-4 from SMP Negeri 6 Pematangsiantar, randomly selected through a lottery method, in which the names of the classes were written on papers and drawn to determine the sample class. The instruments used included 10 multiple-choice questions and 5 essay questions focusing on recount texts. Data were analyzed using descriptive statistics, normality tests, and the Wilcoxon Signed-Rank Test. The findings revealed a significant improvement in students’ reading comprehension after the implementation of the Scanning strategy, with a p-value < 0.001. The results of the Wilcoxon test indicated that the alternative hypothesis (Ha) was accepted, stating that the application of the Scanning strategy significantly enhances students’ reading comprehension abilities. Thus, it can be concluded that the Scanning strategy is effective in improving students’ reading comprehension